2018
DOI: 10.5603/gp.a2018.0086
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation usage by pregnant women in Silesia — population based study

Abstract: Objectives: Despite wide access to gynecological and obstetric advice, informational campaigns, and information online and in magazines aimed at pregnant women, there is a worryingly high percentage of women who still do not use recommended dietary supplementation. The aim of this study was to assess the frequency of micronutrient supplementation by pregnant women and to specify the determinants that impact decisions concerning supplementation. Material and methods:A cross-sectional survey was conducted betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
6
2
Order By: Relevance
“…Fe supplementation is recommended in Poland under specific circumstances (as it was described previously) and our data indicate that it is taken by 24% of the pregnant women. These percentages are lower compared to other data from Poland, where 35% women declared Fe supplementation [43]. It is worth mentioning that the slight differences between studies may be partially a result of different gestational ages within study populations.…”
Section: Discussioncontrasting
confidence: 73%
“…Fe supplementation is recommended in Poland under specific circumstances (as it was described previously) and our data indicate that it is taken by 24% of the pregnant women. These percentages are lower compared to other data from Poland, where 35% women declared Fe supplementation [43]. It is worth mentioning that the slight differences between studies may be partially a result of different gestational ages within study populations.…”
Section: Discussioncontrasting
confidence: 73%
“…We sought to characterize food supplement users and found that primiparous and non-smoking women were more likely to consume food supplements as compared to multiparous and smoking women, with this result being supported by findings from previous studies with both pregnant [ 9 , 34 , 36 , 37 ] and non-pregnant women [ 38 , 39 , 40 ]. Surprisingly, we did not detect an association between supplement use and some factors previously linked with their use during pregnancy such as education, maternal age, or BMI [ 9 , 12 , 13 , 37 , 41 , 42 , 43 , 44 , 45 ]. It could be speculated whether supplement use is linked to a general awareness, irrespective of these factors, of the importance of sufficient nutrient intake during pregnancy for the benefit of the mother and child.…”
Section: Discussioncontrasting
confidence: 94%
“…Previous findings on food supplement use, mostly from cohort studies or clinical trials, indicate that 69–96% of pregnant women use food supplements in Western countries [ 8 , 9 , 10 , 11 , 12 , 13 ]. However, there is little information on the daily intakes of nutrients from food supplements and whether the doses are in line with local recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Fat synthesis is hyperactive, while fat decomposition is suppressed, which often gives rise to fetal macrosomia and premature delivery. 13 , 15…”
Section: Discussionmentioning
confidence: 99%
“…Fat synthesis is hyperactive, while fat decomposition is suppressed, which often gives rise to fetal macrosomia and premature delivery. 13,15 Both prenatal subclinical hypothyroidism and vitamin D deficiency are common diseases in the first trimester. They can produce adverse effects in pregnant women and fetuses.…”
Section: Discussionmentioning
confidence: 99%